Changing the World : American Progressives in War and Revolution - Dawley, Alan, 1943-2008 (Book collections on Project MUSE., 2003)
In May of 1919, women from around the world gathered in Zurich, Switzerland, and proclaimed, ""We dedicate ourselves to peace!"" Just months after the end of World War I, the Womens International League for Peace and Freedom--a group led by American progressive Jane Addams and comprising veteran campaigners for social reform--knew that a peaceful world was essential to their ongoing quest for social and economic justice. Alan Dawley tells the story of American progressives during the decade spanning World War I and its aftermath. He shows how they laid the foundation for progressive.